Effect of sea buckthorn extract on production performance, serum biochemical indexes, egg quality, and cholesterol deposition of laying ducks - Yao, Bing-nong; Liao, Fu-you; Yang, Jiao-yi; Liu, Ai; Wang, Jiao; Zhu, Bao-guo; Feng, Gang; Yang, Sheng-lin (Frontiers in Veterinary Science, 2023)
The purpose of this study was to add different proportions of sea buckthorn extract(SBE) on the production performance, serum biochemical indexes, egg quality and cholesterol deposition of laying ducks. 240, 23-week-old laying ducks (female ducks) with similar body weight, which were randomly divided into 4 groups, with 6 replicates in each group, and 10 ducks in each replicate. The experimental groups were fed diets supplemented with 0, 0.5 g/kg, 1.0 g/kg and 1.5 g/kg of SBE, respectively. The results showed that the addition of 1.0 g/kg SBE to the diet significantly increased (P < 0.05) the average egg weight and feed conversion ratio of laying ducks. The inclusion of SBE significantly increased (P < 0.05) the yolk weight, shell strength, egg white height and haugh unit of duck eggs. Feeding 1.0g/kg and 1.5g/kg SBE significantly reduced (P < 0.05) yolk cholesterol. SBE may improve (P < 0.05) the total amino acid content of eggs (P < 0.05) and the contents of essential amino acids, non-essential amino acids, umami amino acids, monounsaturated fatty acids and docosahexenoic acids (DHA) in eggs. Supplementation with SBE to the diet reduced (P < 0.05) the contents of total saturated fatty acids, polyunsaturated fatty acids, n-3 polyunsaturated fatty acids and n-6 polyunsaturated fatty acids in duck eggs. SBE reduced (P < 0.05) the levels of serum TC, TG and LDL-C, while increased (P < 0.05) the levels of serum SOD, T-AOC and GSH-Px. Additionally, SBE could improve the levels of serum IgG, IgA and IgM in laying ducks (P < 0.05). The addition of SBE to diets can improve feed nutrient utilization, increase egg weight, egg quality and amino acid content in eggs, reduce blood lipids in ducks, improve fatty acid profile and yolk cholesterol in eggs, and increase antioxidant capacity and immunity in laying ducks.